Photochemical modification of a diamond surface using a pulsed UV laser as the energy source - Silva, Mariana (2024)
Funding Information: Funding by FCT/MCTES (Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia) through national funds (PIDDAC) and, where applicable, co-financed by the European Regional Development Fund (FEDER) is acknowledged by LAQV-REQUIMTE (Ref. UIDB/50006/2020 , doi 10.54499/UIDP/50006/2020 ), by Instituto de Telecomunica\u00E7\u00F5es (Refs. UIDB/50008/2020 - UIDP/50008/2020 and PTDC/EEI-TEL/1511/2020 ), by CICECO (Refs. UIDB/50011/2020 , doi 10.54499/UIDB/50011/2020 ; UIDP/50011/2020 , doi 10.54499/UIDP/50011/2020 ; LA/P/0006/2020 , doi 10.54499/LA/P/0006/2020 ) and by i3N (Refs. LA/P/0037/2020 , UIDP/50025/2020 and UIDB/50025/2020 ). NES acknowledges the FCT PhD scholarship 2022.09798. RO acknowledges the FCT contract CEECIND2021.01066. JD acknowledges the FCT contract CEECINST/00102/2018. Publisher Copyright: © 2024 The Authors